Theoretical study of the problem of creative thinking by Eastern and Western thinkers - Rustamova Manzura Ne'matjanovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Creativity acts as the Supreme administrator of social life, human activity, further improving a person's ability to think, and directs him towards good deeds. Such a creative person is always actions in harmony with being. Considered one of the most important social qualities that represent a person's humanity, the concepts of “creative ability” and “creative thinking” are one of the most important signs that represent the independence of an individual at the same time, while testifying to the fact that a person is a person with a high creative capacity